A Study on the Plant Litter Decomposition Using Mycoflora for Sustainable Environment - Singh, Raj; Upadhyay, Sushil Kumar (Plantae Scientia, 2019)
Most of the agricultural, forest and field crop litters are consisting lignocelluloses, cellulose, hemicellulose and lignin. Among these cellulose is most predominant constituent followed by hemicellulose and lignin. The lignin together with the hemicellulose, encrust the cellulose chains forming a barrier which prevents wetting and access of cellulose-degrading enzymes therefore, the decomposition of litters can be achieved by breaking this association at first. The biodegradation of lignin of field crop litters representing a key step for carbon recycling in land ecosystem, as well as for industrial utilization of plant biomass, humification of dead organic matter by the application of certain bacterial and fungal species. The present study revealed the process of decomposition of plant litters. The fungal species colonized different types of plant litters on the basis of enzymatic activities and resource specificity. The mixtures of microorganisms could degrade lignocellulosic materials of wheat stubbles more efficiently than any individual species; Aspergillus niger, Aspergillus flavus, Aspergillus terreus, Fuserium equiseti, Trichoderma lignorum and Stachybotrys atra. A mixture of fungi and Streptomyces caused 48.0% decomposition while decomposition by an individual species viz. Aspergillus flavus was 36.90% only. It was found that, fungi have better abilities to decompose wheat straw than bacteria and actinomycetes. The mineralisation of plant residues could accelerate the rate of decomposition.